Diabetic foot problem in Nepal - Baral, Suman; Rajbhandari, Satyan (Frontiers in Endocrinology, 2023)
Nepal is a developing country where diabetes is becoming a major health challenge due to its high prevalence of 8.5% affecting around 2 million people. Due to limited resources, there are many barriers to providing affordable and convenient diabetes care or regular screening for complications. There is no reliable data on incidence, prevalence, and complications of diabetic foot problems in Nepal. We conducted a survey amongst senior physicians, who were members of ‘Diabetes & Endocrine Association of Nepal’ to assess their perception of diabetic foot problems in Nepal. Thirty Eight physicians responded to the survey who saw a total of 17597 patients in the preceding month. They recalled seeing 647 with 'Diabetic Foot Ulcers', giving a crude Diabetic Foot Ulcer prevalence rate of 3.7%. They recalled seeing 2522 patients with painful neuropathy that required medical treatment, giving a crude painful neuropathy prevalence rate of 14.3%. A history of foot ulcer was present in an additional 578 patients. Previous minor amputation had been performed in 215 patients (1.2%) and major amputation in 135 patients (0.8%). Despite having expertise in various fields there is no dedicated multi-disciplinary diabetic foot clinic in Nepal. This survey shows that diabetic foot problems are abundant in Nepal and there is a need for structured multi-disciplinary approach for screening and treatment.